Research on cost allocation for interorganisational systems. (26th May 2009) - Deng, Libin; Liu, Zhenyu
Interorganisational Systems (IOSs) play an increasing role in information exchange and resource sharing across organisational boundaries. But designing and implementing IOSs needs an extraordinary amount of specific capital investment that should be fairly allocated among cooperative members. Although numerous researches have been conducted on IOSs from interdisciplinary areas, unfortunately few have been done on the cost analysis of IOSs. This paper shifts attention to cost allocation for IOS, which is a critical part of guaranteeing efficient cooperation. First, this paper analyses the content of cost for IOSs, and then, based on various considerations, proposes the Stackelberg game model to analyse the cost allocation mechanism between a core firm and its partners. Results show that when a member's return on IOSs increases, the cost proportion increases as well. In addition, when the risk of IOSs is up within a certain range, the proportion of cost for partners rises, while it decreases for the core firm. These results are consistent with the simulation.